2010
DOI: 10.1161/hypertensionaha.110.155689
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of Ecto-5′-Nucleotidase by Rosuvastatin Increases the Vasodilator Response to Ischemia

Abstract: Abstract-3-Hydroxy-3-methyl-glutaryl-coenzyme A reductase inhibitors (statins) are effective in the primary and secondary prevention of cardiovascular events. Although originally developed to improve lipid profile, statins have demonstrated a surplus of beneficial pleiotropic effects, including improved endothelial function, reduced inflammation, and increased tolerance to ischemia-reperfusion injury. In preclinical studies, increased ecto-5Ј-nucleotidase activity, the key enzyme in extracellular adenosine for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 43 publications
0
25
0
Order By: Relevance
“…Only recently, Haskó and co-workers (21) demonstrated that ecto-5NT decreases mortality and organ injury during murine sepsis. Interestingly, recent studies in animals and in humans in vivo have shown that statins cause an activation of ecto-5NT activity (14,22,23). Furthermore, it was recently demonstrated that the use of statins during intensive care unit stay reduces hospital mortality (24), but whether an increase in extracellular adenosine accounts for the survival benefit needs to be further explored.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only recently, Haskó and co-workers (21) demonstrated that ecto-5NT decreases mortality and organ injury during murine sepsis. Interestingly, recent studies in animals and in humans in vivo have shown that statins cause an activation of ecto-5NT activity (14,22,23). Furthermore, it was recently demonstrated that the use of statins during intensive care unit stay reduces hospital mortality (24), but whether an increase in extracellular adenosine accounts for the survival benefit needs to be further explored.…”
Section: Discussionmentioning
confidence: 99%
“…Enzyme activity assays for ADA, AK, and ecto-5NT were performed as previously described (13,14). In summary, PBMCs were washed three times in sterile PBS.…”
Section: Enzyme Activity Assays (Ada Ak and 5nt)mentioning
confidence: 99%
“…Focal ischemia also increased the activ-ity of cerebroprotective e5'NT, which may increase the levels of neuroprotective Ado [63,118,126,344,345]. Rosuvastatin increased the extracellular levels of Ado via an enhancement of e5'NT activity and, as a consequence, increased the vasodilatator response to ischemia [346]. Upregulation of e5'NT activity was also demonstrated in models of brain damage, such as the cortical stub injury [347,348].…”
Section: Modulation Of 5'-nucleotidase Activity: a New Promising Thermentioning
confidence: 94%
“…Previous studies demonstrated that statins (3-hydroxy-3-methylglutarylcoenzyme A reductase inhibitors) reduce serum low-density lipoprotein (LDL) cholesterol, which is associated with a significant reduction in cardiovascular events. [1][2][3][4] Statins also have cholesterol-independent pleiotropic effects, such as upregulation of ecto-59-nucleotidase, [5][6][7][8] activation of the phosphatidylinositol 3-kinase-Akt pathway, 9 activation of the ERK 1/2 pathway 10 and upregulation of nitric oxide (NO) synthase. 11,12 These pleiotropic actions may contribute to the cardioprotective effects of statins, such as an improved tolerance against ischemia and reperfusion injury (IR injury).…”
Section: Introductionmentioning
confidence: 99%